Virtual Screening of Mimosa pudica Secondary Metabolites as Hyaluronidase B Potential Inhibitor to Prevent Vespa velutina Venom Spreading - Rijalullah, Muhammad Asyraf; Pramudya, Muhammad Alif Imam; Maisuroh, Dalilatul; Zain, Dhiyaa Syahlaa Bianca Febrinnisa; Kurniawan, Nia; Fatchiyah, Fatchiyah (JSMARTech: Journal of Smart Bioprospecting and Technology, 2021)
Vespa velutina, also known as the Yellow-legged hornet, is a wasp species native to Asia with a large distribution area in Indonesia. Hyaluronidase B in a wasp venom acts as a "spreading factor", which is the key at the beginning of envenomation. Shameplant (Mimosa pudica), a common plant in Indonesia, has shown the potential to be a hyaluronidase B inhibitor. This study aimed to analyze the potential of secondary metabolites in Shameplant as an inhibitor of V. velutina Hyaluronidase B base on their molecular interactions and as a topical drug base on physicochemical characteristics. In silico computational studies is performed to predict the binding modes of M. pudica compounds and hyaluronidase B enzyme. The secondary metabolites were retrieved from the PubChem database and screened using SwissADME. The seven metabolite compounds were docked with Hyaluronidase B and hyaluronan by HEX Cuda 8.0.0 program. Hyaluronidase B was also docked with its native ligand (hyaluronan) to validate the docking study. Three dimensional and 2D views were then evaluated using Discovery Studio 2016. Results of this study are all compounds do not have the same molecular interaction with the control. It defines no inhibition of the interaction on the active side. Mimopudine is the most potent inhibitor of hyaluronidase B based on its binding energy. While, jasmonic acid is the only compound that meets the physicochemical parameter of the topical drug.